2018
DOI: 10.1016/j.clml.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Parameters of Hematologic and Immunologic Function and Patient Well-being in the Phase III RESONATE Study of Ibrutinib Versus Ofatumumab in Patients With Previously Treated Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma

Abstract: Ibrutinib led to significant improvements in hematologic function and disease symptomatology versus ofatumumab, and can restore quality of life while prolonging survival in relapsed/refractory CLL/SLL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 30 publications
2
35
0
2
Order By: Relevance
“…Median platelet count at baseline was 105 (range, 2–310) × 10 9 /l in PCYC‐1102 and 117 (range, 20–441) × 10 9 /l in PCYC‐1112; 45% and 38% of patients, respectively, had platelet count <100 × 10 9 /l and 12% and 11%, respectively, had platelet count <50 × 10 9 /l. In both studies, we observed an increase in platelet count over time (Barrientos et al , ; Byrd et al , ). Concomitant anticoagulation or antiplatelet therapy was common; 35 patients (11%) received anticoagulants, 110 (34%) received antiplatelet agents and 30 (9%) received both (Table , Table SI).…”
Section: Resultssupporting
confidence: 60%
“…Median platelet count at baseline was 105 (range, 2–310) × 10 9 /l in PCYC‐1102 and 117 (range, 20–441) × 10 9 /l in PCYC‐1112; 45% and 38% of patients, respectively, had platelet count <100 × 10 9 /l and 12% and 11%, respectively, had platelet count <50 × 10 9 /l. In both studies, we observed an increase in platelet count over time (Barrientos et al , ; Byrd et al , ). Concomitant anticoagulation or antiplatelet therapy was common; 35 patients (11%) received anticoagulants, 110 (34%) received antiplatelet agents and 30 (9%) received both (Table , Table SI).…”
Section: Resultssupporting
confidence: 60%
“…These results show that changes in clinical stage separate the iwCLL PR/PR‐L response category into different, clinically meaningful, subgroups and reinforces the notion that improving cytopenias is a desirable goal of CLL therapy (Barrientos et al , ). Changes in clinical stage could be a useful and inexpensive method to evaluate treatment response at different time points over the course of the disease.…”
Section: Baseline Characteristics By Binet Staging For Partial Responsupporting
confidence: 81%
“…Historically, chemotherapy treatment for hematologic malignancies was associated with significant numbers or severity of AEs and quality-of-life burdens (26,27). Targeted therapies like acalabrutinib have the potential for more favorable AE profiles and are less likely to be associated with quality-of-life decrements (12,28). Our data show that the combination of acalabrutinib plus obinutuzumab did not decrease patients' quality of life.…”
Section: Research Articlementioning
confidence: 70%